A Descriptive Analysis of the Fastest Race Courses for Triathletes - Mabliny Thuany; David Valero; Elias Villiger; Marilia Andrade; Katja Weiss; Pantelis T. Nikolaidis; Rodrigo Luiz Vancini; Thomas Roseman; Beat Knechtle (Baltic Journal of Sport and Health Sciences)
Background: For Ironman® triathlon, it has been reported that most of the fnishers and the fastest women and men in Ironman® Hawaii originated from the United States of America (USA). We have, however, no knowledge of where the fastest race courses in the Ironman® 70.3 triathlon took place. We aim to analyse where the Ironman® 70.3 races were held and where the fastest split and overall race times were achieved.